Protection of the human aortic valve interstitial cells against radiation-induced remodeling by repression of the TRPM4 channel - Aize, Margaux; Brard, Laura; Kerevel, Corentin; Boilève, Arthur; Mpweme Bangando, Harlyne; Touihar, Maysan; Roussel, Benoit D; Lebrun, Alexandre; Saplacan, Vladimir; Manrique, Alain; Simard, Christophe; Guinamard, Romain (American Journal of Physiology: Cell Physiology, 2025)
Radiation-induced aortic valve deleterious remodeling may occur years after radiotherapy. The transient receptor potential melastatin 4 (TRPM4) cation channel participates in aortic valve radiation-induced remodeling in mice in vivo. Valvular interstitial cells (VICs) are involved in valve leaflet thickening and calcification leading to aortic stenosis. TRPM4 favors their remodeling toward an osteogenic phenotype in vitro. Here, we evaluated whether radiation-induced remodeling involves TRPM4 in human valvular interstitial cells (hVICs). VICs were isolated from aortic valves and maintained in procalcifying media supplemented or not with 9-phenanthrol (a TRPM4 inhibitor) or small hairpin RNA (shRNA)-TRPM4. Cells were irradiated at 0 Gy or 8 Gy. Ten days after irradiation, cell surface, viability, cycle, and proliferation were measured. Senescence was evaluated by β-galactosidase activity measurements. Osteogenic markers [bone morphogenetic protein 2 (BMP2), runt-related transcription factor 2 (Runx2), and alkaline phosphatase (ALP)] and TRPM4 mRNA levels were quantified by quantitative polymerase chain reaction (qPCR). VIC surface increased after radiation, whereas cell density decreased. Radiation had no effect on viability but induced an increase in the proportion of cells in G0 cell cycle phase. An increase of cell senescence was observed after irradiation. Finally, irradiation induced an increase of TRPM4, BMP2, Runx2, and ALP mRNA. All these effects were partly prevented by 9-phenanthrol or shRNA-TRPM4. Interestingly, VIC density on aortic valve leaflets from mice submitted to X-ray treatment in vivo was decreased in treated animals compared with untreated ones, and this was not observed in animals with disruption of the gene. TRPM4 participates in radiation-induced hVICs remodeling by promoting cell senescence and osteogenic transition. TRPM4 may, thus, be evaluated as a therapeutic target to diminish valvular effects of radiotherapy. The paper demonstrates, by pharmacological and molecular approaches, that the TRPM4 cation channel is involved in radiation-induced osteogenic remodeling of human valvular interstitial cells in culture. Osteogenic remodeling and cell senescence are prevented by TRPM4 inhibition. Since interstitial cells participate in aortic valve remodeling leading to aortic stenosis such as observed in some patients treated for cancer with radiotherapy, TRPM4 inhibition might be evaluated as an interesting new target to avoid this deleterious side effect.